Spectroscopic Analysis of Ammonium Nickel Sulphate Solution (International Journal of Scientific Research in Science and Technology, 2024)
Using double-beam UV/Vis spectrophotometer, the spectrum absorbed by the solution of Ammonium Nickel Sulphate (H8N2NiO8S26H2O) determined, and the relationship between concentration and absorption was graphed. Using a cuvette containing distilled water in the reference cell and Ammonium Nickel Sulphate with a concentration of 0.0871 mole/litre in the sample cell, absorption was measured at various wavelengths.
Keywords: Double Beam UV-Visible Spectrophotometer